Peer influence and family factors as correlate of academic achievement of high ability girls in secondary schools in Owerri, Imo State (2016)
It has become obvious that it is difficult to determine factors that have direct relationship with academic achievement of students, most especially the high ability girls in our secondary schools. It is on this basis that this study investigated peer influence and family factors as correlate of academic achievement of high ability girls in secondary schools in Owerri, Imo State, Nigeria. The study adopted the descriptive survey research design of the ex-post facto type. Simple random sampling technique was used to select ten secondary schools in Owerri, Imo State. Ten purposively selected from each school making a total of one hundred (100) participants. The main participants were instruments used for the study include: Slosson Intelligence Test (S1T), Student Academic Record as well as Family Cohesion, Broken Home, Parental Socio-Economic Status, Peer Influence and Academic Achievement Questionnaire (FaBSPAQ) developed by the researchers. Data were analysed using simple per cent age and Pearson's Product Moment correlation at the 0.05 level of significance. Findings revealed that, there is a positive and significant relationship between broken home and family cohesion (r=0.461), parental socio-economic status related to family cohesion r=0.539, and parental socio-economic status with broken home r=0.594. Peer influence has a relationship with family cohesion r=0.457 and parental SES r=0.308 respectively. Therefore, there is relationship among the independent variables but not statistically significant. Findings also revealed that none of the four independent variables has any significant effect or contribution to the prediction of academic achievement among high ability girls with family cohesion (β = -.066, t = - .500 p>0.05), broken home, (β= -031, t =236p>0.05), parental SES (β= -.189p>0.05),and peer influence (β= -128, t = -1.114 p>0.05). Finally, the findings revealed that there is no significant combined influence of independent variables to the prediction of dependent variable. The ANOVA result of the regression analysis shows that there was no- significant joint influence of the independent variables on academic achievement. The model summary table revealed that adjusted R2 of 1.21% of the variance observed in the achievement of the student which was statistically not significant. F (4,95) = .742, p>0.005. it is therefore recommended that schools, parents and researchers should identify other factors that may affect the academic achievement of high ability girls. Recommendation was also made that parents should promote unity at home as this may promote positive emotional status of high ability girls which in turn could lead to improved academic achievement.